Revisiting women’s role in world Christianity: A theological analysis of John 4:1–42 - Gharbin, Godibert K.; van Eck, Ernest (Verbum et ecclesia, 2025)
A recent study reveals that women predominantly make up global Christian congregations. However, because of religio-cultural influences – common to both the contemporary and New Testament worlds – the contributions of women often go unrealised. For instance, John 4:1–42 illustrates how Christ’s response to the Samaritan woman prevented the suppression of her contributions to Christianity. This study utilises Osborne’s theological analysis to examine John’s proposed solutions to these challenges, as it explores how the theological and dynamic dimensions of narratives convey theological ideas. This approach enables readers to reconstruct John’s theological perspective on women’s roles in global Christianity. The findings suggest that an encounter with Jesus must transcend religio-cultural barriers that marginalise women, thereby enabling them to fulfil their divinely appointed roles within global Christianity.Intradisciplinary and/or interdisciplinary implicationsThe characterisation of the Samaritan woman’s encounter with Jesus challenges gender-based marginalisation and redefines gendered roles in global Christianity. Therefore, the research intersects with missiology, sociology and anthropology.